Mengintegrasikan Kecerdasan Buatan dalam Pembelajaran Fisika: Studi Pemanfaatan ChatGPT pada Materi Gelombang Optik - Yanto, Nurfitra; Muhiddin, St. Mutia Alfiyanti (Journal of Health, Education, Economics, Science, and Technology, 2025)
This study aims to assess how the effectiveness of ChatGPT and the extent to which ChatGPT technology can improve students ' understanding of optical wave materials. This study used a descriptive-quantitative Survey research design. The results showed that the average student prospective science teacher needs to chat four times to understand one problem on optical wave material this shows that ChatGPT can be a tool for students to answer a problem without asking again to the lecturer.  ChatGPT can be used as a tool in understanding the main learning material in physics which describes a lot of material that tends to be abstract so that it takes time for students to understand it. However, in the use of ChatGPT, there is also a need for supervision and application of academic ethics so that the integrity of learning outcomes is maintained.